Information exchange across borders and confidentiality rights of taxpayers from a South African perspective - Britton, Phillipa (Department of Finance and Tax, 2016)
In light of the provisions of the Tax Administration Act, No 28 of 2011 (TAA), as well as the introduction of Tax Information Exchange Agreements (TIEAs) between South Africa and other nations around the world, the issues around information exchange and the confidentiality thereof has become pertinent. Article 26 of the Organisation of Economic Co-operation and Development (OECD) Model Tax Convention on Income and on Capital provides a standard for information exchange and also highlights the use of automatic exchange of information as being considered a standard form of information exchange. The recent case of Commissioner of South Africa v Werner Van Kets dealt with the definition of a taxpayer as well as information exchange. In addition, this case ruled on the hierarchy of domestic laws and international agreements. This case has led to the question of whether or not a third party is considered a taxpayer in terms of international tax agreements and raises question regarding the taxpayer's rights to confidentiality relating to information exchanged. In light of new international best practice, domestic legislation and case law, various domestic laws of South Africa were reviewed to determine whether the domestic law allows for the international exchange of information and whether or not the confidentiality clauses therein are contradictory to one another. When reviewing the manner in which South Africa allows for the exchange of information, in light of the standard Article 26, it was found that the TIEAs are aligned with both the TAA and Article 26 in terms of the exchange of information that is relevant to domestic laws. It would however appear that South Africa has not yet adopted the use of automatic exchange of information - apart from the Foreign Account Tax Compliance Act (FATCA) Inter-Governmental Agreement (IGA) that was signed with the USA. South Africa has only entered into bilateral agreements which allow for the exchange of information on request and The TAA is silent on automatic exchange, despite the financial benefit of increased annual taxation revenue that South Africa could gain through having automatic exchange agreements in place.